Socialist Realism Markers in Biopics "Taras Shevchenko" - Matiychak, Aliona; Nikoriak, Natalia (Shota Rustaveli Institute of Georgian Literature. Georgia, Tbilisi., 2023)
The dynamics of the interpretation of Kobzar image in the film biographies "Taras Shevchenko" (1926) and "Taras Shevchenko" (1951) is quite demonstrative in the realm of the general formation specificity of the "pantheon of heroes" of the Soviet regime. Still in the 1926 biopic by P.Chardynin the first attempts to adapt Shevchenko's biography and creative heritage to the needs of Soviet ideology were made. Architectonically the film consists of a series of novellas chronicling the writer's life –from childhood to his death. However, the biographical canvas is filled with socialist realism codes, creating a "convenient" image for the Soviet authorities. Traditional Soviet ideologemes appear in the 1926 biopic: "a prophet-kobzar", "an autodidact artist-serf", "a rebel", "a fighter for the liberation of the oppressed and dejected". This film is believed to start the creation of a new image of Kobzar as "a forerunner of modern communist ideas." The 1951 film by I. Savchenko, shot on the eve of 90th anniversary of Kobzar's death, was a confirmation of the paradigm shift. Here, the attention is focused on the period of Shevchenko's exile, on his sufferings in the captivity. The film creates a heroic image of Shevchenko as "a symbol of the proletarian struggle" and "a fighter for socialist ideals". Soviet mythologemes actively appear in the 1951 biopic – "a poet-fighter", "a ‘petrel’ of the revolution", "a peasant poet", "a younger brother of the Russian social democrats". The film became a demonstrative example of the embodiment of the ideological socialist realism narrative and cinematographic Shevchenkiana had to be guided by it in the following decades.
Keywords: "Taras Shevchenko"; P.Chardynin; I.Savchenko; biopic